Construction of Questionnaire-Scale USOTIC "Social Networks in Primary and Secondary School Students: Use and Digital Coexistence" - María Carmen López Berlanga; Luis Ortiz Jiménez; Cristina Sánchez Romero (MDPI AG, 2022)
In the present work, the construction process, namely the design, elaboration and validation of a questionnaire-scale is described to evaluate the attitudes and interactions in the way of living in the digital world of social networks in primary and secondary students. The current aim was to analyse the means, uses and risks, as well as the sources of training and advice those students have to interact with the diverse range of devices with an internet connection that provide access to social networks. The participating sample for validation was 1073 students from the Primary and Secondary Education stages of centres with organic dependency: Private, concerted and public. The obtained results express the satisfactory metric quality of the questionnaire, thus presenting a theoretically based and operationally defined instrument, considering four relevant dimensions: Special, environmental, perceptual and motivational.